Risk factors for eating disturbance in adolescent girls with dysregulation of the menstrual cycle - A. A. Pichikov; E. V. Volkova; Y. V. Popov; Y. A. Yakovleva A. (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева, 2020)
Summary. The article presents the results of eating behavior and personality traits study in a group of adolescent girls who consulted a gynecologist in connection with menstrual irregularities.The aim of the study was to identify risk factors for eating disturbance in adolescent girls with menstrual dysregulation.Materials and methods: were examined 75 adolescent girls with various disorders of the menstrual cycle (amenorrhea, opsooligomenorrhea, menorrhagia) and 25 girls of the control group. The characteristic features of eating disorders, the degree of dissatisfaction with one’s appearance, the level of self-esteem, various aspects of self-attitude, the severity of perfectionism and the level of anxiety were assessed. The main factors that determine the relationship between eating behavior and personal characteristics were identified using factor analysis. Risk factors for the development of the main symptoms of eating disorders (drive for thinness and bulimia) in adolescent girls were assessed using regression analysis.Results. It was found that girls with menstrual irregularities are more prone to episodes of overeating and the use of cleansing procedures, they have lower self-esteem and a more negative self-attitude. There were no significant differences in the girls’ assessment of their body image depending on the presence or absence of menstrual irregularities, as well as on the type of disturbances. This assessment in all cases had a tendency to negative perception of varying severity. Factor analysis of indicators of eating disturbances and personality traits in the study groups showed that eating disturbances in girls are closely associated with a negative attitude towards their bodies and with indicators of anxiety. Regression analysis identified indicators affecting drive for thinness and bulimic behavior that differed between groups.Conclusion. Eating behavior in adolescent girls is mediated through various psychological characteristics, including those associated with the features of the menstrual cycle.